If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(n + 5) + 3(n + 1) = 0 Reorder the terms: 6(5 + n) + 3(n + 1) = 0 (5 * 6 + n * 6) + 3(n + 1) = 0 (30 + 6n) + 3(n + 1) = 0 Reorder the terms: 30 + 6n + 3(1 + n) = 0 30 + 6n + (1 * 3 + n * 3) = 0 30 + 6n + (3 + 3n) = 0 Reorder the terms: 30 + 3 + 6n + 3n = 0 Combine like terms: 30 + 3 = 33 33 + 6n + 3n = 0 Combine like terms: 6n + 3n = 9n 33 + 9n = 0 Solving 33 + 9n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + 9n = 0 + -33 Combine like terms: 33 + -33 = 0 0 + 9n = 0 + -33 9n = 0 + -33 Combine like terms: 0 + -33 = -33 9n = -33 Divide each side by '9'. n = -3.666666667 Simplifying n = -3.666666667
| 5x+18=13x-44 | | 3x-(6x-5)=-55 | | 1200x1/3 | | 3(n+2)+4(n+3)= | | 1200•1/3 | | x=(96-x) | | 7x-8x-10=x+2 | | 6-1.5b+1=7 | | 8x^2+1=4x^2 | | X-34+X=94 | | (5x-25)(3x+25)= | | s=1.5t-2 | | 2x^4+12x^2-7=0 | | 4a=13*25 | | 1,1,3+x=4,3,4 | | 3x+6=19x-15 | | -2(3n+3)=4 | | 9(y-1)-7(2y+1)=10 | | x+4=-5 | | -12=-3/7z | | 12x-6-12=7+12x-12 | | 2x+8+3x+-6=4findx | | A=j+p | | 6a-3=40 | | 9-2(7x-8x)=4x-3 | | C=5/9(95-32) | | 3x-7x+13x= | | -13+3=-39+17x | | -7c+22=6c-4 | | 3X+5FORX=8 | | 4(4x+7y)=69 | | y^3+15y^2+54y=0 |